The Implementation and Analysis of The Proof of Work Consensus in Blockchain - Therry, Alvin Christian Davidson; Ardiansyah, Rizka; Pusadan, Mohammad Yazdi; Joefrie, Yuri Yudhaswana; Kasim, Anita Ahmad (Advance Sustainable Science, Engineering and Technology, 2024)
Communication in peer-to-peer (P2P) networks presents challenges in maintaining security, data integrity, and decentralization. Consensus mechanisms play a crucial role in addressing these challenges by validating data and ensuring that each entity has synchronized data without intermediaries. This research focuses on the implementation and analysis of the Proof of Work (PoW) consensus mechanism, widely used in blockchain, to enhance understanding of its functions, benefits, and workings or flow. This research, conducted using the Go programming language, successfully implements Proof of Work (PoW) as a security measure, ensuring data integrity, and preventing manipulation. Through black-box testing, this research confirms the functionality and reliability of the implemented Proof of Work (PoW) consensus. These findings contribute to a deeper understanding of consensus mechanisms, offering insights to optimize blockchain protocols and foster trust among entities. This research highlights the relevance of sustainable Proof of Work (PoW) in blockchain technology, emphasizing its role in enhancing security and ensuring data integrity in decentralized networks.